PELAKSANAAN PERLINDUNGAN HAK ATAS PENDIDIKAN BAGI PENYANDANG DISABILITAS (PEOPLE WITH DISABILITY) DI UNIVERSITAS NEGERI GORONTALO - Dion Teguh Pratomo (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract Education is one of the rights that are owned by persons with disabilities who are required to be protected and implemented by the government. Government programs to integrate persons with disabilities into the regular education known as inclusive education. The program issued by the government in this regard is required all universities in Indonesia to organize inclusive education for persons with disabilities through the Minister of Education and Culture No. 46 Year 2014 on Special Education in College one of them is the State University of Gorontalo (UNG). As it is the purpose of this research is to analyze the implementation of the protection of the right to education for persons with disabilities, analyze obstacles in the implementation of protection, as well as analyzing the efforts made by the university in overcoming the obstacles that exist.To answer the problem under study, researchers used a type of research is empirical juridical and approach is juridical sociological research. Based on the research results it can be concluded (1). implementation of the protection of the right to education for persons with disabilities in UNG is not optimal, (2). Barriers experienced by UNG, among others: the unavailability of teaching materials that fit the needs of students with disabilities, the lack of lecturers who have the ability to communicate, the campus that has not been friendly to the disabled, lack of facilities and infrastructure, as well as the lack of funding, (3). Efforts made by UNG, among others: to disseminate relevant campus inclusive of all existing courses, providing infrastructure facilities accessible, organized a friendly learning disabilities, as well as providing lecturers who have skills in communicating with students with disabilities. Key words: Implementation, protection, inclusive education, persons with disabilities Â Abstrak Pendidikan merupakan salah satu dari sekian hak yang dimiliki oleh penyandang disabilitas yang wajib untuk dilindungi dan dilaksanakan oleh pemerintah. Program pemerintah untuk menyatukan penyandang disabilitas ke dalam pendidikan reguler dikenal dengan Pendidikan inklusif. Program yang dikeluarkan oleh pemerintah terkait hal ini adalah mewajibkan seluruh universitas yang ada di Indonesia untuk menyelenggarakan pendidikan inklusif bagi penyandang disabilitas melalui Peraturan Menteri Pendidikan dan Kebudayaan Nomor 46 Tahun 2014 tentang Pendidikan Khusus di Perguruan Tinggi salah satunya adalah Universitas Negeri Gorontalo (UNG). Adapun hal yang menjadi tujuan penelitian dalam penelitian ini adalah menganalisis pelaksanaan perlindungan hak atas pendidikan bagi penyandang disabilitas, menganalisis hambatan di dalam pelaksanaan perlindungan, serta menganalisis upaya yang dilakukan oleh pihak universitas dalam mengatasi kendala yang ada. Adapun metode penelitian yang digunakan adalah jenis penelitian yuridis empiris dengan pendekatan penelitian adalah yuridis sosiologis. Berdasarkan hasil penelitian maka dapat disimpulkan (1). pelaksanaan perlindungan hak atas pendidikan bagi penyandang disabilitas di UNG adalah belum optimal, (2). Hambatan yang dialami oleh UNG antara lain: belum tersedianya bahan ajar yang sesuai dengan kebutuhan mahasiswa difabel, ketiadaan dosen pengajar yang memiliki kemampuan dalam berkomunikasi, lingkungan kampus yang belum ramah terhadap difabel, ketiadaan sarana dan prasarana, serta ketiadaan dana, (3). Upaya yang dilakukan oleh UNG antara lain: melakukan sosialisasi terkait kampus inklusif bagi semua program studi yang ada, menyediakan sarana prasarana yang aksesibel, menyelenggarakan proses pembelajaran yang ramah difabel, serta menyediakan dosen yang memiliki keterampilan dalam berkomunikasi dengan mahasiswa difabel. Kata kunci: Pelaksanaan, perlindungan, pendidikan inklusif, penyandang disabilitas